Tomás González: de la desesperanza, la derrota y otras muertes circulares - Bermúdez, Ronald (2025)
In response to the question “Why are death and violence determining factors in Colombian literary creation?”, this paper seeks to argue the level of coherence in resistant positions that circulate less massively and advocate for ways of perceiving and representing reality that differ from those already institutionalized by the literary industry. The analysis examines four novels by Colombian writer Tomás González (1983, 2000, 2003, 2010), embedded in aesthetic dialogues that define the state of the art of national literature. The conclusion drawn is that the author's narrative not only recreates the dialectic between literary creation and the total collapse of the social universe in which death and violence are represented, but also creates new spaces of meaning.